Triglyceride Mobilization from Lipid Droplets Sustains the Anti-Steatotic Action of Iodothyronines in Cultured Rat Hepatocytes - Grasselli, Elena; Voci, Adriana; Demori, Ilaria; Vecchione, Giulia; Compalati, Andrea D.; Gallo, Gabriella; Goglia, Fernando; De Matteis, Rita; Silvestri, Elena; Vergani, Laura (Frontiers in Physiology, 2016)
Adipose tissue, dietary lipids and de novo lipogenesis are sources of hepatic fatty acids (FFAs) that are stored in lipid droplets (LDs) as triacylglycerols (TAGs). Destiny of TAGs stored in LDs is determined by LD proteomic equipment. When adipose triglyceride lipase (ATGL) localizes at LD surface the lipid mobilization is stimulated. In this work, an in vitro model of cultured rat hepatocytes mimicking a mild steatosis condition was used to investigate the direct lipid-lowering action of iodothyronines, by focusing, in particular, on LD-associated proteins, FFA oxidation and lipid secretion. Our results demonstrate that in ‘steatotic’ hepatocytes iodothyronines reduced the lipid excess through the recruitment of ATGL on LD surface, and the modulation of the LD-associated proteins Rab18 and TIP47. As an effect of ATGL recruitment, iodothyronines stimulated the lipid mobilization from LDs then followed by the up-regulation of carnitine-palmitoyl-transferase (CPT1) expression and the stimulation of cytochrome-c oxidase (COX) activity that seems to indicate a stimulation of mitochondrial function. The lipid lowering action of iodothyronines did not depend on increased TAG secretion. On the basis of our data, ATGL could be indicated as an early mediator of the lipid-lowering action of iodothyronines able to channel hydrolyzed FFAs towards mitochondrial beta-oxidation rather than secretion.